Technology and research progress of Anammox bacteria immobilization - LUO Jiaxin; ZHANG Dachao; SU Hao; ZHANG Runhuan (Gongye shui chuli, 2024)
The Anammox technology has great application value in the treatment of wastewater with high ammonia-nitrogen and low carbon nitrogen ratio as its low energy consumption and high nitrogen removal efficiency. However, the application of Anammox nitrogen removal technology is limited due to the slow growth rate of autotrophic Anammox bacteria, the easy loss of sludge and the strict requirements for growth environment. This paper summarized the principles, advantages, disadvantages and applicable scenarios of the four major Anammox bacteria immobilization technologies, and presented the latest research progress of these Anammox bacteria immobilization technologies. The carrier materials used in different immobilization methods were introduced, and the key influencing factors and optimum conditions of Anammox bacteria immobilization technology were summarized. Finally, the deficiency of the Anammox bacteria immobilization technology and the future research direction were summarized and prospected, so as to provide some research ideas for the further development of this technology.